Pengaruh Kepuasan Konsumen Terhadap Loyalitas Pelanggan Pada PT. Telkomsel Di Wilayah Tarakan - Anwar, Syaiful (Ekonomika, 2010)
The Purpose Of This Study To Test The Influence Of Customer Satisfaction On Customer Loyalty In The PT Telkomsel In City Of Tarakan. Analysis Tool Used Multiple Linear Regression. The purpose of using Multiple Regression in this study to determine the effect of Call Quality (X1), Pricing Structure (X2), Mobile Devices (X3), Value Added Sevices( X4), Convenience In Produceres (X5) and The Customer Support (X6), of the customer loyality variables (Y) at PT Telkomsel Tarakan. From the results of calculations performed to find the result that the value-added factor services is the highest factor influencing customer loyalty to the services product of PT. Telkomsel. Value added services affect customer loyalty to the PT. Telkomsel is about 22,70% with the assumption that other variables constant. Key Words : Customer Satisfaction, Customer Loyalty